2007
DOI: 10.1016/j.prevetmed.2007.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Livestock farmers’ perception and epidemiology of bovine trypanosomosis in Kwale District, Kenya

Abstract: We did cross-sectional surveys in Kwale District, Kenya to determine the epidemiology of bovine trypanosomosis and livestock owners' perceptions of the disease. The surveys involved relative importance of trypanosomosis, examination of the current disease constraints, current control practices and drug-use patterns. Informal meetings were held with farmers and cattle census undertaken. Tsetse-fly densities and trypanosomosis prevalences in cattle were determined. A total of 132 farmers were interviewed. Trypan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
23
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 9 publications
17
23
1
3
Order By: Relevance
“…The parasitological examination revealed a prevalence rate of 33.9% for bovine trypanosomosis with T. congolense 56.06% and Trypanosoma vivax 43.94% being the pathogenic trypanosomes identified. This study is in agreement with the findings of other researchers in various parts of Africa (Leak, 1999;McDermott et al, 2003), but our finding differed with previous data collected in the same Division by Ohaga et al (2007) and also from Orma Boran cattle raised in Galana Ranch (Coastal Province in Kenya), over the past decade (1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000) indicated that there were significantly higher T. vivax infections in cattle as compared to T. congolense infections (Bett et al, 2004). Probably Localities where infections were due to T. vivax could be an indication of the presence of other potential haematophagus insect vectors other than tsetse flies.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The parasitological examination revealed a prevalence rate of 33.9% for bovine trypanosomosis with T. congolense 56.06% and Trypanosoma vivax 43.94% being the pathogenic trypanosomes identified. This study is in agreement with the findings of other researchers in various parts of Africa (Leak, 1999;McDermott et al, 2003), but our finding differed with previous data collected in the same Division by Ohaga et al (2007) and also from Orma Boran cattle raised in Galana Ranch (Coastal Province in Kenya), over the past decade (1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000) indicated that there were significantly higher T. vivax infections in cattle as compared to T. congolense infections (Bett et al, 2004). Probably Localities where infections were due to T. vivax could be an indication of the presence of other potential haematophagus insect vectors other than tsetse flies.…”
Section: Discussionsupporting
confidence: 91%
“…Result of tsetse and biting flies apparent densities confirm earlier findings by Ohaga et al (2007) which observed that G. austeni, G. brevipalpis, G. pallidipes and biting flies were present in the survey area. Great variability in tsetse apparent densities observed by location could be explained by the fragmentation of tsetse habitat along riparian vegetation as described by Rocque et al (2001).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This coupled with their knowledge on the signs of the disease and treatment suggests that the farmers have comparable understanding of the problem as reported earlier [9,25,31] in other African countries.…”
Section: Discussionsupporting
confidence: 74%
“…Similarly, studies conducted in tsetse-infested areas of Ethiopia [10,13,26,27], Kenya [9,25,33] and other west African countries [31] have revealed that most of the interviewed livestock farmers were able to mention the common symptoms that are used as diagnostic tool for trypanosomosis suspected cases.…”
Section: Discussionmentioning
confidence: 96%